Perencanaan Reklamasi Dengan Revegetasi Pada Stockpile Di PT. Allied Indo Coal Kecamatan Talawi, Kotamadya Sawahlunto, Provinsi Sumatera Barat - Fauzan Azim; Yunasril Yunasril (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Allied Indo Coal is a public company that conducts coal mining activities with the type of company PKP2B (Coal Mining Concession Agreement) under contract No. J2 / Ji.Du / 25/1985 on August 21, 1985. The mining contract period is 32 years with an area of 372.40 Ha.Reclamation with revegetation activities will be carried out in some part of the stockpile area, stockpile area to be reclaimed consists of 3 blocks, block 1 has an area about 0.83 ha, the block 2 about 1.46 ha and block III about 2.91 Ha. The total area to be revegetated in the reclamation activity about 5.2 ha. Because of PT.Allied Indo Coal has a license from forestry department (IUP) to exploit a forest area a so the company has an obligation to pay the land compensation, includes PNBP fees (Non-tax State Revenues). This stockpile is one of the areas subject to the PNBP (Non-tax State Revenue) with a tariff of Rp. 3,900,000 / ha every month. So that this activity aims to reduce the burden of PNBP (Non-tax State Revenues) to the company tax.Reclamation activities include land management activities. The land is recovered with overburden at the bottom and then the upper layercovered with top soil as a growing medium for plants. After the land arrangement is complete, the cover crop will be planted. Furthermore, the revegetation process starts from irrigation, digging planting holes, planting, and maintenance.Based on calculations in reclamation planning with revegetation, the direct costs for revegetation reclamation activities in Stockpile at PT. Allied Indo Coal is IDR 804,921,900.00. and indirect costs are IDR 173,101,842.00. Then the total cost of reclamation and revegetation at that location is IDR978,023,742.00.Keywords: Stockpile, PNBP, Reclamation Plan, Revegetation, Cost.